All that Glitters Is not Gold: Consumer Health Informatics and Education in the Era of Social Media and Health Apps - Fernandez-Luque, L.; Staccini, P.; Section Editors for the IMIA Yearbook Section on Consumer Health Informatics (Yearbook of Medical Informatics, 2016)
Objective: To summarize the state of the art published during the year 2015 in the areas related to consumer health informatics and education with a special emphasis on unintended consequences of applying mobile and social media technologies in that domain.Methods: We conducted a systematic review of articles published in PubMed with a predefined set of queries, which lead to the selection of over 700 potential relevant articles. Section editors screened those papers on the title, abstract, and finally complete paper basis, taking into account the papers’ relevance for the section topic. The 15 most representative papers were finally selected by consensus between the two section editors and submitted for full review and scoring to external reviewers and the yearbook editors. Based on the final scoring, section editors selected the best five papers.Results: The five best papers can be grouped in two major areas: 1) Digital health literacy and 2) Quality and safety concerns. Regarding health literacy issues of patients with chronic conditions such as asthma, online interventions should rather focus on changing patient beliefs about the disease than on supporting them in the management of their pathology since personally controlled health management systems do not show expected benefits,. Nevertheless, encouraging and training chronic patients for an active online health information–seeking behaviour substantially decreases state anxiety level. Regarding safety and privacy issues, even recommended health-related apps available on mobile phones do not guarantee personal data protection. Furthermore, the analysis indicated that patients undergoing Internet interventions experienced at least one adverse event that might be related to treatment. At least, predictive factors have been identified in order to credit or not a health rumour.Conclusions: Trusting digital and connected health can be achieved if patients, health care professionals, and industrials build a shared model of health data management integrating ethics rules. Only increasing efforts in education with regards of digital health would help reach this goal., This would not resolve all frauds and security issues but at least improve their detection.
Keywords: Health literacy; confidentiality; patient safety; e-health; internet, social media